The Influence Of Communication And Leadership On Job Satisfaction (Census On WO Squad.id Association Members Tasikmalaya) - Jajang Sulaeman Lesmana; Kusuma Agdhi Rahwana; Arga Sutrisna (Penerbit Jurnal Indonesia, 2022)
This study aims to determine the effect of communication and leadership on job satisfaction of members of the WO Squad.id association. The method used is causal associative with a reserch sample of 50 respondents from members of the WO Squad.id association. The data used is primary data. The analytical tool used in this study is multiple linear regression using SPSS version 25. The results showed that the communication felt by the members of the WO Squad.id association members has very good criteria. Leadership of the WO Squad.id association members has very good criteria. Simultaneously, communication and leadership have a significant effect on job satisfaction. Partially comunication has a significant effect on job satisfaction. Partially, leadership has a significant effect on job satisfaction.